Effect Of Soil Shear Strength on Shoreline Changes at Batu Pahat Coastal Area - Mokhtar, Mardiha; Daud, Mohd Effendi; Sabri, Muhamad Syamil (Journal of Sustainable Underground Exploration, 2022)
This study focuses on the effect of soil shear strength due to the shoreline changes in Batu Pahat Coastal Area. The shorelines of Pantai Punggur were chosen as the subject location for this investigation on soil shear strength and shoreline changes of eroded areas in Batu Pahat, Johor. Pantai Punggur is situated on the west coast of Johor, with a latitude of 1.62° to 1.87° N and a longitude of 102.78° to 103.19° E. Aerial photographs and field observation data were used to determine the geomorphological components of the Pantai Punggur shoreline using an unmanned aerial vehicle (UAV). The study conducted is to produce shoreline changes mapping diagram and analysis soil shear strengths across different sampling locations were measured and correlate with shoreline changes at zones A, B, C, D and E. The aerial image that has been captured by the drone was analyzed using Pix4D and Global Mapper software. Based on the data of shoreline changes zone A portrays the highest changes followed by zone B and C. As for zone D and E its shows quite a small change. Within one month interval, Pantai Punggur coastline experiences changes in about 1.57 meters. From the undrained shear strength test at 0.5 m depth at HT and MT data for December 2021, zone A with Cu reading are more than 4.5 kPa followed by zones B, C, D and lowest at zone E. Next, at depth 0.5 m and 1.0 m data for December 2021 at HT level, zone A with Cu reading is more than 4.5 kPa at the 0.5 m and 1.0 m depth and other zones are below than 3.0 kPa. The depth of soil also influences the data of this study. The correlation of changes in soil shear strength with shoreline changes is reported to have a linear correlation with R2 value is 0.9261. It can conclude that the effect of soil shear strength on shoreline changes at Batu Pahat coastal area cause by the changes in soil shear strength (Cu) gives a large effect of shoreline changes.